An Exploration of Ethical and Methodological Challenges in Trans-Afrmative Psychotherapy with Filipino Transgender and Gender Non-Conforming (TGNC) Clients. - Salvador, D. L.
To spark critical and professional discussion on integrating transafrmative psychotherapy in clinical and counseling psychologists? general practice, this paper presents and describes some ethical and methodological challenges in doing trans-afrmative psychotherapy with Filipino transgender and gender non-conforming (TGNC) clients, specifcally transgender women. Sources of insight for this paper include: a) case notes and observations from a research-therapy project with two transgender client-participants, b) the author?s observations from previous clinical work with LGBT clients, and c) the literature on TGNC mental health outcomes and trans-afrmative practice. The challenges described here pertain both to ethical boundaries that circumscribe the practice of psychotherapy and counseling as well as to principles that undergird methodologically sound or efective clinical work. Some proposed resolutions to these highlight the importance of thinking integratively about the ethical and methodological dimensions of practice work.
Keywords: Pscyhology -- Periodicals; Transgender; Trans-affirmative.; Therapy; Psychotherapy; Counseling